DETERMINANTS OF INDONESIA’S SHRIMP EXPORTS TO THE UNITED STATES - Muhammad Raihan Basyar; Ida Ayu Meisthya Pratiwi (Adisam Publisher, 2026)
Shrimp is a leading commodity in Indonesia’s fisheries sector and plays a crucial role in generating non-oil and gas foreign exchange earnings, with the United States serving as the primary destination market, absorbing more than 60 percent of total exports. However, Indonesia’s shrimp export volume to the United States declined during the 2022–2024 period, despite continuous growth in consumer income in the destination country. This condition indicates the presence of structural challenges in the competitiveness of Indonesia’s shrimp exports. This study aims to analyze the effects of international shrimp prices, consumer income proxied by United States GDP per capita, and the exchange rate on the volume of Indonesia’s shrimp exports to the United States over the period 1995–2024. The study employs a quantitative approach using secondary time-series data. The analytical method applied is Multiple Linear Regression with a First Difference transformation to address data stationarity issues, estimated using the Ordinary Least Squares (OLS) method.The results show that, simultaneously, international prices, consumer income, and the exchange rate have a significant effect on Indonesia’s shrimp export volume. Partially, international prices have a positive and significant effect, consistent with supply theory, which suggests that higher global prices encourage an expansion of export supply. In contrast, United States GDP per capita has a negative and significant effect, indicating that Indonesian shrimp tends to be treated as an inferior good in a developed-country market. Meanwhile, the exchange rate does not have a significant effect on export volume, supporting the Dominant Currency Paradigm. This study recommends accelerating fisheries downstreaming and improving production efficiency to enhance sustainable export competitiveness.